Humane forest landscape forest restoration approach in San Mariano, Isabela - Taylan, Aegirine Rei M.; Navarra, Nappy L. (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
This study proposes Humane Forest Landscape Restoration as a comprehensive approach to combat loss in San Mariano, Isabela, Philippines. Forests in the region are valuable resources, providing essential services to the community and environment. However, they are threatened by destructive human activities and natural disturbances. By integrating the human aspect into restoration efforts, this study proposes a holistic and sustainable approach that considers social, economic and ecological dimensions of forest restoration. The research methodology involves preliminary research, objective formulation, and an extensive literature review. Primary and secondary data were collected through site visits, biotope mapping, consultations, interviews, and literature reviews. Thematic analysis, forest management unit mapping and DPSIR analysis were employed to analyze the date and develop three planning scenarios : agricultural development, agroforestry development, and ecotourism development. Through an assessment based on the principles of humane forest landscape restoration (enhancing livelihood, inclusiveness and equity, economic diversification, and capacity building), agroforestry development emerged as the most suitable option. The study proposes specific areas and interventions within the agroforestry scenario, along with implementation and maintenance guidelines. By implementing humane forest landscape restoration, the study shall contribute to the preservation and sustainable management of forests, fostering a resilient ecosystem that supports local communities' well-being while preserving the area's ecological integrity for present and future generations.
include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Agroforestry -- San Mariano (Isabela).; Forest degradation -- San Mariano (Isabela).; Forest restoration -- San Mariano (Isabela).